Implementation of Tax Incentives on Issuers' Financial Ratios: Reduction and Reaction - Yandes, Jufri; Sunarya, Amud; Muhtarom; Destiana (Yayasan Ilomata, 2024)
This study aims to analyze whether the implementation of reduction (deduction) of tax incentives has or does not have a reaction (influence) on the financial ratio (ROE) of shares of IDX issuers LQ45 Index during the COVID-19 outbreak in 2022. The study employs a hypothesis testing approach with classical assumption tests and simple regression analysis, focusing on secondary data from the LQ45 index during the 2022 Covid-19 outbreak. It examined a population of 45, using 36 samples that met specific criteria. A simple linear analysis model was used to investigate the impact, if any, of tax incentive reductions on the financial ratio (ROE) of the issuers' stocks. This study, which uses simple regression analysis, reveals that the implementation of tax incentive reductions made by the Indonesian government does not react (influence) on the financial ratio (ROE) of IDX-listed stocks in the LQ45 Index during the COVID-19 outbreak in 2022. The study suggests that the Indonesian government's tax incentive reductions may not impact the financial ratios (ROE) of companies listed on the IDX, particularly in the LQ45 Index during the Covid-19 outbreak in 2022. This lack of impact is attributed to companies not utilizing these incentives, possibly due to insufficient awareness of their benefits and challenging criteria set by the government for obtaining these incentives. Despite common beliefs that tax incentives can influence financial performance, this study indicates they might not significantly affect the financial ratios of these companies. The real implications is research indicates that the Indonesian government's reduction of tax incentives did not elicit a response in the financial ratio (ROE) of shares issued by LQ45 Index companies on the Indonesia Stock Exchange during the Covid-19 outbreak in 2022. This suggests that the implementation of tax incentive cuts by the Indonesian government had no impact on the financial ratio (ROE) of LQ45 issuer shares during the Covid-19 outbreak in 2022, based on a sample size of 36.